2016
DOI: 10.1016/j.chroma.2016.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Retention behavior of alkyl-substituted polycyclic aromatic sulfur heterocycles in reversed-phase liquid chromatography

Abstract: Retention indices for 79 alkyl-substituted polycyclic aromatic sulfur heterocycles (PASHs) were determined by using reversed-phase liquid chromatography (LC) on a monomeric and polymeric octadecylsilane (C18) stationary phase. Molecular shape parameters [length, breadth, thickness (T), and length-to-breadth ratio (L/B)] were calculated for all the compounds studied. Based on separations of isomeric methylated polycyclic aromatic hydrocarbons on polymeric C18 phases, alkyl-substituted PASHs are expected to elut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Previous studies have observed an early elution for these isomers prior to the unsubstituted parent BbN12T on a smectic liquid crystalline phase, which was attributed to the non-planarity of these two isomers ( T = 4.99 Å and T = 5.32 Å for 11-Me and 1-MeBbN12T, respectively) [13]. Similar observations have been reported for the RPLC separation of these isomers on a polymeric C 18 stationary phase [48]. However, in the present study 11-MeBbN12T does not elute prior to the unsubstituted BbN12T on the 50% LC-DMPS phase.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Previous studies have observed an early elution for these isomers prior to the unsubstituted parent BbN12T on a smectic liquid crystalline phase, which was attributed to the non-planarity of these two isomers ( T = 4.99 Å and T = 5.32 Å for 11-Me and 1-MeBbN12T, respectively) [13]. Similar observations have been reported for the RPLC separation of these isomers on a polymeric C 18 stationary phase [48]. However, in the present study 11-MeBbN12T does not elute prior to the unsubstituted BbN12T on the 50% LC-DMPS phase.…”
Section: Resultssupporting
confidence: 74%
“…The regression calculations for the correlation of L/B and retention on all four stationary phases are summarized in Tables 5 and 6. Wilson et al [47, 48] have recently demonstrated the use of statistical t -test for determining the linear significance of correlation coefficients ( r ) for the retention of isomeric PASHs and MePASHs in RPLC on polymeric C 18 stationary phases and their L/B values using equation 2: titalicexp=rdf1-r2 where df is the degrees of freedom ( n – 2) and n is the number of data points. Based on the df , a significant linear correlation does exist for the correlation coefficient if t exp > t crit [49].…”
Section: Resultsmentioning
confidence: 99%
“…This study provides the most comprehensive investigation of reversed-phase LC retention behavior of PASH to date. A similar study for alky-substituted PASHs is published elsewhere [38]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used correlation coefficients ( r ) as a parameter for measuring the linear correlations for PAH retention and L/B [5, 23, 24]. A statistical test can be performed to test the significance of a correlation coefficient when not close to 1 [44].…”
Section: Resultsmentioning
confidence: 99%
“…In a companion study, the same three stationary phases have been evaluated for the separation of alkyl-substituted PASHs [41]. A similar study has been published investigating the RPLC retention behavior and shape selectivity correlations for the same PASHs [23] and alkyl-substituted PASHs [24]. …”
Section: Introductionmentioning
confidence: 99%